Study of embodied energy in healthcare center construction - García-Sanz-Calcedo, Justo; Neves, Nuno de Sousa; Fernandes, João Paulo Almeida (Journal of Civil Engineering and Management, 2021)
The tendency to build Net-Zero Energy Buildings increases the need to know and control the energy used in them. This research aims to identify and quantify the energy used in the construction of healthcare centres and propose indicators based on different operational variables. For this purpose, seven healthcare centres built between 2007 and 2010 were analysed, and the energy embodied in the manufacturing, transport and placement of materials on-site, including the final tests and commissioning of the building, were calculated. The results show that the average embodied energy is 9.97 GJ per unit of built area, 0.011 for each euro invested in construction and 2.18 GJ for each user. Emissions per worker, construction working hour, electrical power and energy consumed were also typified, and different reference indicators were proposed. Equations have also been devised using multivariate regression to determine the embodied energy of a healthcare centre according to its built area (m2), investment in construction (€) and the number of users (No). The building elements with the most embodied energy were also identified, and the authors found that the average embodied energy is 29.31 times higher than that consumed in a year at the healthcare centre.